Antioxidant Properties of Galangin with β-cyclodextrin: An in Vitro and in Vivo - Zainab Abbas; Ghassan Sulaiman; Majid Jabir; Hamdoon Mohammed; Salman Mohammed (Journal of Applied Sciences and Nanotechnology, 2023)
Galangin, a non-toxic phytochemical, is known to have a variety of therapeutic uses. This study looked into the role of inclusion complexes of galangin/β-cyclodextrin in increasing antioxidant activity over pure galangin. The role of this inclusion complex in increasing antioxidant activity in comparison to pure galangin. In this study, hydrogen peroxide assays were used in vitro. Galangin demonstrated concentration-dependent scavenging action in the 2-50 µg mL-1 range, with the highest level of activity possible 92.00% at 50 µg mL-1. In pure galangin, a decrease of 85.00% was observed. The ferric thiocyanate lipoperoxidation method was clarified by using galangin and galangin/β-cyclodextrin and demonstrated concentration-dependent suppress lipid peroxidation in the 2-50 µg mL-1 range, at 50 µg mL-1, the highest level of activity was 70.00%. A 60.00% decrease in pure galangin was observed. Xanthine oxidase activity using uric acid was given. The co-incubation of galangin and galangin/β-cyclodextrin inhibited xanthine oxidase activity in a concentration-dependent manner in 2-50 µg mL-1 range, at 50 µg mL-1, the highest level of activity was 90.00 %. Pure galangin showed an 82.00 % decrease. There were no significant differences in absolute weight of mice organs and hematological parameters between pure galangin and galangin/ β-cyclodextrin when used concentration 80 mg kg-1, compared to control group. According to the findings, galangin combined with β-cyclodextrin has excellent properties as a therapeutic agent and food supplement.